Investigation of Free Vibration Behavior for Composite Sandwich Beams with a Composite Honeycomb Core - Zainab Majid Jasim; Husam Jawad Abdulsamad (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
The purpose of the current research is to determine the effect of fiber type, volume ratio, and matrix type on the vibration properties of sandwich beams made of composite face sheet and core. The typical sandwich structure consists of three layers: face sheets, core, and adhesive bonding, and in this research, the adhesive layer between the face sheets and core was abolished by preparing the overall mold with fibers inside and casting the resin to fill the face sheet and core parts. The face sheets of the composite beams are made from a polyester or epoxy matrix reinforced with glass fiber, carbon fiber, and hybrid fiber, and the core is a honeycomb consisting of random glass fibers immersed in a resin matrix (polyester or epoxy). 22 composite sandwich beams were constructed to conduct vibration testing. The vibration results obtained experimentally were compared to the ANSYS R1 2022 software, and the results were in very good agreement. Hybrid fibers and polyester matrix achieved the highest values of natural frequency for (clamped-clamped) boundary conditions, where the natural frequency value of the hybrid fiber and polyester matrix reached (2037 Hz) at a volume fraction of (23.14%) experimentally and the natural frequency reached (1804.5 Hz) at a volume fraction of (21.95%) experimentally for the simply supported boundary condition.